The Buffering Effects of Social Insurance for the Spread of Covid-19 - Mirani Ahangarkolaei, Moein; Demir, Eser; Constantinou, Tolga; Toranji, Mostafa; Adino, Tadashi; Tavassoli, Nasrin; Noghani, Atefeh (Information Management and Business Review, 2021)
Global pandemics are associated with substantial losses of human capital. The best strategy of policymakers in public health before a population-wide vaccination is to reduce the outbreak of the disease and finding ways to alleviate its negative consequences in society. Previous studies show that welfare programs have externalities in unintended areas and for unplanned outcomes including a wide range of health outcomes. In this paper, we show that payments under the Unemployment Insurance (UI) program have the potential to reduce the spread of the novel coronavirus. Applying a difference-in-difference technique on monthly data of all US counties from January 2020 to January 2021, we document that the social insurance under the umbrella of UI payments can reduce the transmission rate of Covid-19. The results show heterogeneity across subsample with the largest effects among blacks, poor, and low educated regions